Transgovernance advancing sustainability governance. - Meuleman, Louis (Heidelberg ; New York Springer, 2013)
This book offers a new context for the sustainability governance debate, transforming classical questions into new options for societal decision making and identifying starting points and strategies for effective governance of transitions to sustainability.
Keywords: Non-Profit Enterprises/Corporate Social Responsibility; Sustainable development